Constraint Measures of Production and Future Cultivation Decision of Black Pepper Cultivators of Kerala. - Revathi K Sivadas (International Journal of Research and Analytical Reviews, 2019)
Black pepper, the ‘King of Spices’,it is the most ancient and important spices exported from the ‘ Home of Spices’, India. Indian black pepper and cardamom occupy an enviable place in the international spices market due to their unique quality, flavour and aroma. India, as in the context of these crops, has enjoyed a comparative advantage in quality and natural monopoly. Globally, India contributes the largest area for these crops. Historically black pepper and cardamom in India, which are export-oriented crops and its contribution is sizable. But currently, in India’s production in black pepper has been tiny relative to the area of these crops. As being a perennial crop black pepper faced year to year instability in production and also identified area- production gap became wide in these period.In the spices sector, Kerala is unique and distinct from other major states namely, Karnataka and Tamil Nadu. Kerala accounts 79.7 per cent of pepper production in India.Black pepper production face a lot of challenges and constraints and it categorised into four: cultivation, labour, economic and trade constraints. Because of these constraints, the cultivators are difficult to meet profit condition and it negatively affected future cultivation decision of cultivators on these crops and it analysed through garret ranking and multiple regression method.Thus, regulatory attention is needed for efficient utilisation of available area of spices and it helps to the utilisation of emerging market opportunities underthe globalised era